Minimally invasive versus open surgery in uterine serous carcinoma: impact on recurrence and survival in a multicenter cohort - Fang, Yi; Chen, Jian; Yang, Lin; Lin, Yingtao; Lin, Yao; Lin, Rong; Chen, Xingfa (Frontiers in Oncology, 2025)
BackgroundUterine serous carcinoma (USC) is a highly aggressive subtype of endometrial cancer, characterized by high recurrence rates and poor prognosis. While minimally invasive surgery (MIS) is commonly used in endometrial cancer treatment, its oncologic safety in high-risk USC remains unclear. This study aimed to compare survival outcomes between MIS and open surgery in patients with USC.MethodsIn this multicenter retrospective cohort study, 176 patients with USC who underwent primary surgical treatment were included (MIS: 53 [30.1%], open: 123 [69.9%]). Kaplan–Meier analysis was used to estimate overall survival (OS) and progression-free survival (PFS), while Cox regression identified independent prognostic factors.ResultsThe median follow-up was 78 months (95% CI: 68.3–87.7). Patients in the MIS group experienced a higher recurrence rate (49.1% vs. 31.7%) and lower 5-year PFS (49.7% vs. 68.3%, P = 0.017), although 5-year OS was comparable between groups (69.7% vs. 77.4%, P = 0.219). Multivariate analysis confirmed that MIS as an independent predictor of poorer PFS (HR = 2.29, 95% CI: 1.31–4.01, P = 0.004). In contrast, adjuvant therapy significantly improved PFS (HR = 0.28, 95% CI: 0.13–0.60, P = 0.001). Hypertension was also associated with decreased OS (HR = 2.06, 95% CI: 1.11–3.81, P = 0.022).ConclusionsMIS may be associated with an increased risk of recurrence and reduced PFS in USC patients, while adjuvant therapy remains critical for improving survival outcomes.